The Financial Ratio Analysis as Performance Assessement of Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) BMT Al Hikmah Ungaran - Nur - Haida; Sri Eka Sadriatwati; Saptianing - Saptianing (Admisi dan Bisnis, 2020)
This research was conducted with the aim to find out how healthy the financial performance of KSPPS BMT AL HIKMAH Ungaran 2014 - 2018 based on the Deputy Regulation of the Ministry of Cooperatives and Small and Medium Enterprises Supervision of the Republic of Indonesia Number 06 / Per / Dep.6 / IV / 2016 concerning Guidance on Assessment Savings and Credit Cooperative Health and Cooperative Savings and Loan Unit. This research is based on the calculation of Capital Aspects, Earning Assets Quality Aspects, Liquidity Aspects, and Independence and Growth Aspects by using financial statements in the form of balance sheet and income statement / SHU report for the period 2014 - 2018.  The results showed that the level of financial health in KSPPS BMT AL HIKMAH Ungaran from 2014 - 2018 was still in the title "In Special Supervision". Although it is still far from the title of "Healthy", KSPPS BMT AL HIKMAH Ungaran still has the potential to realize it by continually correcting all deficiencies. This can be seen in 2016 - 2017 which shows an increase in health performance of financial performance with a score of 47.30% compared to 2014 - 2015 which was only able to score 41.89%.